Pembangunan Sistem Informasi Pelaporan Masalah Lingkungan Berbasis Web di Universitas Kristen Satya Wacana - Wijaya, Yemima Clara; Setiyawati, Nina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Meeting environmental challenges necessitates the exploration of new and inventive solutions. The Environmental Quality Index (IKLH) report revealed an uptick in Indonesia's index to 72.42 in 2022 from 71.45 in 2021, despite a worsening air quality trend. Acknowledging the importance of Human Resource Management and